Preoperative Glasgow prognostic score as a predictor of primary bladder cancer recurrence - YUKSEL, OZGUR HAKI (Mol Clin Oncol, 2016)
The correlation between systemic inflammatory markers and malignancies has been assessed by a number of recent studies. The aim of this study was to prospectively assess preoperative inflammation markers and Glasgow prognostic scores (GPS) in patients who underwent surgery for primary bladder cancer (BC), and evaluate the predictive value of GPS for disease recurrence and progression. A total of 38 patients (mean age, 60.16±9.71 years; range, 33–76 years) who were treated in our department between May, 2014 and August, 2015 were enrolled in the present study. Preoperatively, patient information regarding gender, body mass index, serum C-reactive protein (CRP) and albumin levels, GPS and comorbidities, were collected and recorded. Transurethral resection of the bladder was performed, followed by histopathological evaluation of the resected material. The tumor size, stage and grade and the presence of necrosis were determined. According to the international TNM classification, the results of the histopathological analysis were as follows: Ta low- (n=24) and high-grade (n=4); and T1 low- (n=2) and high-grade (n=8). The median follow-up period was 10.1 months (range, 6–12 months). During this period, recurrence was observed in 10 cases and disease progression was detected in 1 patient. Hypoalbuminemia was encountered in 40% of the cases with recurrence, which was significantly higher compared with that in patients without recurrence (7.1%; P=0.031). In patients who had recurrence, a GPS of 1–2 points and tumor necrosis were more frequently detected compared with those without recurrence (60 vs. 7.1%, P=0.002; and 80 vs. 7.1%, P=0.001, respectively). Excluding a cystectomized case with a diagnosis of muscle-invasive BC, disease progression was not detected in any of the cases with recurrence during follow-up. Therefore, we consider that GPS and serum markers of systemic inflammatory response may be used as predictors of recurrence in patients with transitional cell BC.